2006
DOI: 10.1182/blood.v108.11.229.229
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3rd Generation Humanized Type II CD20 Antibody with Glycoengineered Fc and Modified Elbow Hinge for Enhanced ADCC and Superior Apoptosis Induction.

Abstract: Background: Treatment of B-cell non-Hodgkin lymphoma (NHL) with antibodies targeting CD20 in conjunction with combination chemotherapy is standard clinical practice. Two different types of CD20 MAb differing significantly in their mode of CD20 binding and biological activities have been identified (Cragg and Glennie. Blood103: 2738–2743, 2004): type I antibodies, as rituximab, are potent in complement mediated cytotoxicity, whereas type II antibodies, as tositumomab, effectively initiate target cell death via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Recently (in November 2013) it has FDA approved mAb for use in combination with chlorambucil to treat patients with previously untreated chronic lymphocytic leukemia (CLL). Preclinical studies suggested that the modified Fc region of GA101 improved about 50 fold binding affinity to FcγRIII and 10 to 100 fold increased cell death through ADCC mechanism against CD20 positive NHL cell lines [ 57 60 ]. Moreover, in vitro study also demonstrated that modification in elbow hinge regions promotes direct programmed cell death mechanism in several NHL cell lines and primary malignant B-cells [ 12 , 49 ].…”
Section: Development Of Novel Anti-cd20 Mabsmentioning
confidence: 99%
“…Recently (in November 2013) it has FDA approved mAb for use in combination with chlorambucil to treat patients with previously untreated chronic lymphocytic leukemia (CLL). Preclinical studies suggested that the modified Fc region of GA101 improved about 50 fold binding affinity to FcγRIII and 10 to 100 fold increased cell death through ADCC mechanism against CD20 positive NHL cell lines [ 57 60 ]. Moreover, in vitro study also demonstrated that modification in elbow hinge regions promotes direct programmed cell death mechanism in several NHL cell lines and primary malignant B-cells [ 12 , 49 ].…”
Section: Development Of Novel Anti-cd20 Mabsmentioning
confidence: 99%
“…Other antibodies directed against different target proteins in lymphoma and leukemia are under investigation in preclinical and clinical trials. Further improved biological efficacy in NHL might be achieved by combining anti-CD20 rituximab treatment with other antibodies directed against different antigens, such as anti-CD22 [34] or anti-CD40 [35], using humanized antibodies, or using novel anti-CD20 antibodies with modified Fc domains that provide greater affinity for Fc receptors and superior effector functions [36,37].…”
Section: Antibody-based Biological Treatmentsmentioning
confidence: 99%
“…GA-101 (Hoffman La Roche) is a novel third generation fully humanized and optimized anti-CD20 IgG1 differing significantly from other anti-CD20 MAbs, such as rituximab [Fries et al, 2007;Umana et al, 2006]. Using GlycoMab technology, the Fcregion of GA-101 was glycoengineered to contain bisected, afucosylated carbohydrates.…”
Section: Ga-101mentioning
confidence: 99%